A composite measure of performance–expectation and performance-only measures. Issue 15 (10th December 2017) - Park, Sang-June; Yi, Youjae
ABSTRACT: Performance–expectation measures and performance-only measures of service quality have been widely used in the literature. However, either of the two measures is not sufficient to explain customers' evaluation of service quality and satisfaction. Their assumptions are too restrictive to explain the evaluation processes. From an analytic perspective, this paper derives a composite measure integrating both measures for service quality. The previous measures are nested in the composite measure. Due to this feature, the composite measure is more flexible than the previous measures. It can account for conflicting theories and empirical findings supporting each of the two measures. Furthermore, the composite measure allows us to interpret the link between service quality and customer satisfaction more intuitively.